Hypoxia‐induced phrenic long‐term facilitation: emergent properties. (26th March 2013) - Devinney, Michael J.; Huxtable, Adrianne G.; Nichols, Nicole L.; Mitchell, Gordon S.
Abstract : As in other neural systems, plasticity is a hallmark of the neural system controlling breathing. One spinal mechanism of respiratory plasticity is phrenic long‐term facilitation (pLTF) following acute intermittent hypoxia. Although cellular mechanisms giving rise to pLTF occur within the phrenic motor nucleus, different signaling cascades elicit pLTF under different conditions. These cascades, referred to as Q and S pathways to phrenic motor facilitation (pMF), interact via cross‐talk inhibition. Whereas the Q pathway dominates pLTF after mild to moderate hypoxic episodes, the S pathway dominates after severe hypoxic episodes. The biological significance of multiple pathways to pMF is unknown. This review will discuss the possibility that interactions between pathways confer emergent properties to pLTF, including pattern sensitivity and metaplasticity. Understanding these mechanisms and their interactions may enable us to optimize intermittent hypoxia‐induced plasticity as a treatment for patients that suffer from ventilatory impairment or other motor deficits.